Self: a concept in development - Macedo, Lídia Suzana Rocha de; Silveira, Amanda da Costa da (Paidéia (Ribeirão Preto), 2012)
Many definitions for the self coexist in the psychological theory and praxis. This diversity is a result of epistemological basis from which different strategies are selected in order to approach, describe and limit the target object. This paper aims to provide a review on concepts concerning the self and a reflection on how this concept is articulated in different Psychology theoretical approaches. The impact of the central dilemmas of developmental Psychology to the concept of self is also discussed. Thus, this paper suggests a systematic approach in order to analyze each self definition: One should seek to answer how each theory has positioned itself in relation to the dicotomies of stability versus transformation, specific versus universal, and inner world versus external world.